Contribution Of The Creative Economy Sector To Economic Growth And Labor Absorption In Pangkalpinang - Dhias Latria; Yuristian Eka Prakarsa; Reniati Reniati; Ari Agung Nugroho (International Conference On Digital Advanced Tourism Management And Technology, 2023)
The study aims to investigate the relationship between the contribution of the creative economy sector to economic growth and employment in Pangkalpinang City. In the constantly changing context of the global economy, the creative economy sector has emerged as one of the major growth engines, with the main focus of research covering two key aspects, namely Poverty Dynamics and Population Activity of 15 Years and Up. Data analysed from 2016 to 2021 by exploring the types of training organized by the Tourism, Culture, Youth and Sports Department of Bangka Belitung Islands. The research uses methods of secondary data analysis involving economic data, employment, and creative economic sectors. The study identifies some creative subsectors that have greater growth potential than others. These sector-specific analyses provide a deeper insight into how different segments of the creative economy can more effectively contribute to the economic development of Pangkalpinang City. Implications of these findings are the need to develop stronger and more targeted policy strategies to support the growth of the creative economy sector.This research provides an in-depth understanding of the role of the creative economy sector in supporting economic growth and labour absorption in Pangkalpinang. The conclusions emphasized the need for inter-sectoral policy synergies and support for the growth of the creative sector of the economy in a holistic way. The implications of these findings could be the basis for more informed and sustainable policy planning in Pangkalpinang.